The best in children's nonfiction : reading, writing, and teaching Orbis Pictus Award books - Jensen, Julie M.; Kerper, Richard M.; Zarnowski, Myra, 1945- (Urbana, Ill. : National Council of Teachers of English, 2001)
Profiles the writings which have won the NCTE's award for excellence in children's nonfiction over the last ten years and explains how the committee chooses the award-winning books.
Includes bibliographical references (p. [101]-154).
Reference and Research Book News.
Wilson's Children.
Professional
Keywords: Children's literature, American -- Bibliography; Children's literature, American -- History and criticism; Orbis Pictus Award; Children's literature -- Bibliography; Children's literature -- History and criticism; Orbis Pictus Award